Відображення українського національного руху Галичини в журналі «Киевская старина» (1882–1906 рр.) - Райківський, Ігор; Raikivskyi, Igor (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті висвітлено відображення на сторінках журналу «Киевская старина» українського руху в Галичині. Редакція підтримувала діяльність галицьких народців, давала уявлення про слабкість зв’язків підросійської України з краєм, що відіграли особливу роль у процесі формування ідеї української національної єдності. The article of magazine «Kyevskaya staryna» describes a reflection of Ukrainian national movement in Galicia. In particular, the attention is payed to publications of Galicia history in the context of relations of local population with Poles and Russians. The articles in Galician topics of famous Ukrainian leaders such as M.Kostomarov, V.Antonovych, Ja.Holovats’ky, the editor of the magazine V.Naumenko etc are analysed. The edition supported people movement, the activity of local «Prosvita» and T.Shevchenko organization, where they criticised moskvofils, who were called «quasi-velykorusy». The magazine gave an idea about weakness of relations between Russian Ukraine and Galicia, but regularly contained the information about Rusyn-Ukrainian’s life under Austrian authorities, that promoted formation process of Ukrainian national unity idea in public consciousness.
Reflection of Ukrainian National Movement of Galicia in the Magazine «Kyevskaya staryna» (1882-1906)
Keywords: журнал; громадське життя; національний рух; національна єдність (соборність); Галичина; magazine; public life; national movement; national unity; Galicia